2020
DOI: 10.31234/osf.io/uqb7a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Identification and Collective Action Participation in the Internet Age: A Meta-Analysis

Abstract: There is a debate about the dynamics of participation in collective actions in the Internet age whether different or not from the engage in conventional ones. Some scholars claimed that the role of shared social identity is relatively unimportant in the Internet age. In order to clarify whether collective actions in the digital age still rely on social identification or not, we conducted a meta-analysis of 40 studies (N = 16,933) focused on digitally-mediated collective actions. We examined the relationship be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 59 publications
3
9
0
Order By: Relevance
“…Rather, they are impelled by participants’ shared desire for social change, which provides the base for forming a new ingroup and developing the corresponding social identity (Smith, Gavin, & Sharp, 2015; Smith, Thomas, & McGarty, 2015). In conclusion, our results support the idea that classical psychological variables (i.e., social identity, injustice, and efficacy) still matter (for review, see Akfırat et al, 2021; Priante et al, 2018). In the present context, protestors had a strong identification with the group emerging from the Gezi Park protests; they perceived acute injustices related to police brutality and the decision to demolish the park, and they felt that together they could challenge the government and the police.…”
Section: Discussionsupporting
confidence: 87%
“…Rather, they are impelled by participants’ shared desire for social change, which provides the base for forming a new ingroup and developing the corresponding social identity (Smith, Gavin, & Sharp, 2015; Smith, Thomas, & McGarty, 2015). In conclusion, our results support the idea that classical psychological variables (i.e., social identity, injustice, and efficacy) still matter (for review, see Akfırat et al, 2021; Priante et al, 2018). In the present context, protestors had a strong identification with the group emerging from the Gezi Park protests; they perceived acute injustices related to police brutality and the decision to demolish the park, and they felt that together they could challenge the government and the police.…”
Section: Discussionsupporting
confidence: 87%
“…Findings from the social identity approach to collective action show that, at the individual level, social identification correlates strongly with measures of normative collective action but much less so with nonnormative ones (Mahfud & Adam-Troian, 2019;Tausch & Becker, 2011 .13] with nonnormative collective action searches. Again, the positive links between plural FPP and measures of normative collective action were within the range of recent metaanalytical estimates from studies using individual-level measures for both constructs (.38 < r < .52; see Akfirat et al, 2020).…”
Section: Measurement Validitysupporting
confidence: 78%
“…This is exactly what happened in France and our data suggest that the creation of the new Yellow Vest identity is the critical social‐psychological process that allowed the growth of the movement. In contrast, there was no support for the view that social‐psychological predictors of protest are now secondary, given the development and use of new communication technologies (see Akfirat et al., 2020; Lee et al., 2017).…”
Section: Studymentioning
confidence: 99%
“…While the work of McPhail and Miller (1973) suggests an affirmative answer, research addressing the impact of social media use on collective action is mixed (for a review see Akfirat et al., 2020; Kende et al., 2016; Priante et al., 2018). For example, Schumann and Klein (2015) showed that online participation can sometimes decrease actions offline, a phenomenon known as slacktivism.…”
Section: Introductionmentioning
confidence: 99%